2021
DOI: 10.1177/10732748211050581
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Clinical Utility of Circulating Tumor Cells at Different Time Points in Predicting Prognosis of Patients With Small Cell Lung Cancer: A Meta-Analysis

Abstract: Objectives Numerous studies have elucidated that circulating tumor cells (CTCs) have significant prognostic value in various solid tumors. However, the prognostic value of CTCs in small cell lung cancer (SCLC) remains controversial. The current study was performed to investigate the prognostic significance of different time points of CTCs in SCLC. Methods PubMed, EMBASE, Web of Science, and Cochrane Library databases were retrieved for eligible studies. Pooled hazard ratios (HRs) and 95% confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…CTCs seem highly promising for clinical cancer management, based on their non-invasive, easily repeatable, and dynamic real-time monitoring analysis ( 145 ). Additional CTC markers have been explored in NSCLC patients treated by ICI.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…CTCs seem highly promising for clinical cancer management, based on their non-invasive, easily repeatable, and dynamic real-time monitoring analysis ( 145 ). Additional CTC markers have been explored in NSCLC patients treated by ICI.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Furthermore, at this juncture, we have a real field to maneuver, as many studies have indicated that both structures with high sensitivity and specificity can be used as a liquid biopsy in the diagnosis and prognosis of patients' outcomes and responses to treatment [36,44,91]. Nevertheless, many meta-analyses have confirmed the unique diagnostic and prognostic value of CTCs [92][93][94][95]. The same properties are attributed by meta-analyses to circulating EVs [96][97][98][99].…”
Section: Advantages Limitations Pros and Consmentioning
confidence: 99%
“…134 The analysis of CTC number at baseline and at different time points in the course of SCLC was referred to for the prediction and monitoring of the response to chemotherapy. 135 Circulating tumor cells obtained from plasma samples may be also used for the detection of specific mutations related to lung cancer, such as EGFR 136 and KRAS, 137 with a higher sensitivity than ctDNA. Moreover, specific gene rearrangements can be detected in CTCs with promising acurracy.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%